2022
DOI: 10.1111/jcmm.17224
|View full text |Cite
|
Sign up to set email alerts
|

Joint efficacy of the three biomarkers SNCA, GYPB and HBG1 for atrial fibrillation and stroke: Analysis via the support vector machine neural network

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia, 1 affecting 33 million people worldwide annually. 2 Given the association between AF, obesity, hypertension and other rapidly growing health problems, its prevalence is projected to double over the next 30 years. 3 AF is associated with a threefold to fivefold increased risk of stroke, 4 and AF-related strokes are typically severe, causing significant long-term physical disability and cognitive dysfunction, high mortality and healthcare costs, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…In agreement with previous studies, the GO annotations related to HBD are oxygen transport, iron ion binding, blood coagulation, and combination with oxygen (Chen et al, 2020). In previous studies, we found that HBG1/HBD may induce the occurrence and development of AF through inflammation and hemoglobin levels (Wang et al, 2022). We need further studies to evaluate the clinical implications of our results and whether patients with atrial fibrillation will benefit from the antiinflammatory effects of edoxaban.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with previous studies, the GO annotations related to HBD are oxygen transport, iron ion binding, blood coagulation, and combination with oxygen (Chen et al, 2020). In previous studies, we found that HBG1/HBD may induce the occurrence and development of AF through inflammation and hemoglobin levels (Wang et al, 2022). We need further studies to evaluate the clinical implications of our results and whether patients with atrial fibrillation will benefit from the antiinflammatory effects of edoxaban.…”
Section: Introductionsupporting
confidence: 91%
“…Through the immunofluorescence assay, compared with the red blood cells of the control individuals, the expression of HBG1 was higher in the red blood cells of the patients with atrial fibrillation (Wang et al, 2022) (p < 0.05, Figure 1A). In addition, the expression of HBD was also higher in the red blood cells of the patients with atrial fibrillation than in those of the control individuals (p < 0.05; Figure 1B).…”
Section: Expressions Of Hbg1 and Hbd In The Red Blood Cells Of The Pa...mentioning
confidence: 99%
“…IFIT1 [51] might be involved in the pathogenesis of atherosclerosis. HBG1 [52] is important in the development of atrial fibrillation. RAP1GAP [53] was associated with cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 957 DEGs including 477 up regulated and 480 down regulated genes were identified. Wang et al [44] and Joshi et al [45] showed altered expression of HBG1 and S100A8 in cardiovascular diseases. Lu et al [46] reported that S100A8 promoted cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%